Correlation Between Arrhythmia and the Prognosis in Children With EFE/LVNC/DCM - Wang, Hong; Chu, Yan-Qiu; Yu, Xian-Yi; Chen, Rui; Xing, Yan-Lin; Yu, Xue-Xin; Wang, Ce; Sun, Le; Xu, Yun-Ming; Li, Xue-Mei; Cui, Xiao-Zhe (Frontiers in Pediatrics, 2020)
AIM: To explore the correlation between different phenotypes of arrhythmia and the prognosis in children with cardiomyopathy. METHODS: A total of 167 children with cardiomyopathy diagnosed and treated in Shengjing Hospital between January 2010 and May 2019 were evaluated. After patient screening, 31 patients with endomyocardial fibroelastosis (EFE), left ventricular non-compaction, or dilated cardiomyopathy with significant arrhythmias were selected. Follow-up was undertaken 0, 1, 3, 6, 9, or ≥12 months after treatment. RESULTS: We revealed the outcomes for five types of cardiomyopathy: EFE with Wolff–Parkinson–White syndrome and supraventricular tachycardia; EFE with intraventricular block; EFE with complete left bundle branch block; EFE with atrial flutter and atrial fibrillation; EFE with ventricular tachycardia. CONCLUSION: The long-term prognosis of cardiomyopathy in children is related to the type of arrhythmia and time of intervention. The earlier arrhythmia is controlled, the better is the prognosis. Pre-excitation syndrome type-B, especially a significantly broadened QRS interval, carries a poor prognosis if radiofrequency ablation is not undertaken.